Operation efficiency of laboratories in county-level centers for disease control and prevention in China: a data envelopment analysis - Yuan-lei LI; Zheng KANG; Xiao-ning HAO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo evaluate operation efficiency of laboratories in county-level centers for disease control and prevention (CDCs) in China for providing evidences to decision-making on improvement of operation efficiency of the laboratories and optimization of health resources allocation.MethodsUsing systematic sampling and a self-designed questionnaire, we conducted onsite or letter surveys among 19 laboratories in county-level CDC of 3 provinces (Anhui, Guangdong and Sichuan) in 2020. Data envelopment analysis (DEA) was adopted to evaluate overall, technical and scale efficiency of the laboratories in 2019; projection analysis was also employed to identify shortcomings in the laboratories' operation.ResultsFor all the laboratories in 2019, the average index values were 0.766, 0.879, and 0.868 for overall, technical, and scale efficiency, respectively. Of the laboratories, 63.2% were assessed as in the state of deficiency in overall operation and only 26.4% were evaluated as having an increasing scale efficiency in terms of scale benefit. Projection analysis revealed that the resources allocated in the laboratories were not utilized sufficiently and both the number of samples/specimens detected and test reports issued should be increased to achieve operation efficiency based on DEA.ConclusionAt present in China, the operation efficiency of laboratories in county level CDCs is at a low grade and the allocated resources were not sufficiently utilized by the laboratories; the situation should be concerned by governmental agencies in decision-making.